Renal reabsorption in 3D vascularized proximal tubule models - Lin, Neil Y. C. (Proc Natl Acad Sci U S A, 2019)
Three-dimensional renal tissues that emulate the cellular composition, geometry, and function of native kidney tissue would enable fundamental studies of filtration and reabsorption. Here, we have created 3D vascularized proximal tubule models composed of adjacent conduits that are lined with confluent epithelium and endothelium, embedded in a permeable ECM, and independently addressed using a closed-loop perfusion system to investigate renal reabsorption. Our 3D kidney tissue allows for coculture of proximal tubule epithelium and vascular endothelium that exhibits active reabsorption via tubular–vascular exchange of solutes akin to native kidney tissue. Using this model, both albumin uptake and glucose reabsorption are quantified as a function of time. Epithelium–endothelium cross-talk is further studied by exposing proximal tubule cells to hyperglycemic conditions and monitoring endothelial cell dysfunction. This diseased state can be rescued by administering a glucose transport inhibitor. Our 3D kidney tissue provides a platform for in vitro studies of kidney function, disease modeling, and pharmacology.